The Dimensions of Legal Opinion's Role in Settlement of Civil Law Cases - May Shinta (IHSA Institute, 2022)
Legal opinion is a doctrine that was originally used for the legal practic. Doctrine is a source of the law. The legal opinion has a function to be able to resolve cases or acts against the law, whether it's a criminal and civil law cases. Legal opinions are usually used as directions or instructions for the community when experiencing a legal problem. usually clients come to lawyers to assist him in solving the problem. The problem that will be discussed in this research is the dimension of legal opinion in solving civil law problems. While the research method used is a qualitative research method with an empirical juridical approach. The results of this study indicate that legal opinion is a dynamic and easy alternative in solving civil law problems. Legal opinion is also a dimension of civil case settlement that can be used as a basis in addressing and finding the best solution for a legal problem that is being experienced. While the purpose of legal opinion is to describe a legal contextual either explicitly or implicitly.